Measuring intrinsic and extrinsic motivation factors drive to loyalty at Pejabat Tanah Dungun, Terengganu / Nik Norhafiza Nik Mohd Sukrri - Nik Mohd Sukrri, Nik Norhafiza (2014)
The purpose of conducting this study is to identify the relationship between intrinsic and extrinsic motivation and loyalty at Pejabat Tanah Dungun, Terengganu. This study has six objectives. The first objective is to examine which factor between intrinsic and extrinsic can increase loyalty among employees at Pejabat Tanah Dungun. The second objective is to compare between male and female employees who are highly influenced by the intrinsic motivation at Pejabat Tanah Dungun. The third objective is to compare between male and female employees who are influenced by the extrinsic motivation at Pejabat Tanah Dungun. The fourth objective to compare between male and female employees that influence at Pejabat Tanah Dungun. The fifth objective is to determine the relationship between intrinsic factors towards loyalty at Pejabat Tanah Dungun. The sixth objective is to determine the relationship between extrinsic factors towards loyalty at Pejabat Tanah Dungun. This study utilized convenience sampling techniques. The data of this study is collected using questionnaires which require respondents to rate the motivation level for them to be loyal in an organization. Likert scales are used to get the results. The comparison is measured using regression. Based on the findings, there is a positive relationship between intrinsic, extrinsic and loyalty. Even though their level of loyalty is low, most of the employees have been working for more than 15 years.